THE ROLE OF AI IN DEVELOPING MULTIMODAL AND DIGITAL WRITING LITERACIES (Multidisciplinary Journal of Science and Technology, 2026)
The integration of artificial intelligence (AI) into educational environments has transformed the landscape of writing instruction, particularly in the domains of multimodal and digital literacies. In tertiary education, students are increasingly required to produce texts that combine linguistic, visual, auditory, and interactive elements, often with the assistance of AI-powered tools. This paper examines the role of AI in developing multimodal and digital writing literacies among university students. Employing a mixed-method design with 200 undergraduate students and 25 instructors across four universities, the study explored how AI tools such as generative text models, image creators, and digital editing platforms influence students' ability to design, compose, and critically evaluate multimodal texts. Results indicate that AI significantly enhances students' technical fluency, design experimentation, and efficiency in mode-switching. However, challenges persist in critical AI evaluation, ethical attribution, and preservation of authorial voice. The findings underscore the necessity of integrating AI literacy into writing curricula, emphasizing a balanced approach where AI serves as a collaborative scaffold rather than a substitute for human creativity and critical thinking.